Patients With Inflammatory Bowel Disease Show IgG Immune Responses Towards Specific Intestinal Bacterial Genera - Bourgonje, Arno R.; Roo-Brand, Geesje; Lisotto, Paola; Sadaghian Sadabad, Mehdi; Reitsema, Rosanne D.; de Goffau, Marcus C.; Faber, Klaas Nico; Dijkstra, Gerard; Harmsen, Hermie J. M. (Frontiers in Immunology, 2022)
Introduction Inflammatory bowel disease (IBD) is characterized by a disturbed gut microbiota composition. Patients with IBD have both elevated mucosal and serum levels of IgG-antibodies directed against bacterial antigens, including flagellins. In this study, we aimed to determine to which intestinal bacteria the humoral immune response is directed to in patients with IBD. Methods Fecal and serum samples were collected from patients with IBD (n=55) and age- and sex-matched healthy controls (n=55). Fecal samples were incubated with autologous serum and IgG-coated fractions were isolated by magnetic-activated cell sorting (MACS) and its efficiency was assessed by flow cytometry. The bacterial composition of both untreated and IgG-coated fecal samples was determined by 16S rRNA-gene Illumina sequencing. Results IgG-coated fecal samples were characterized by significantly lower microbial diversity compared to the fecal microbiome. Both in patients with IBD and controls, serum IgG responses were primarily directed to Streptococcus, Lactobacillus, Lactococcus, Enterococcus, Veillonella and Enterobacteriaceae, as well as against specific Lachnospiraceae bacteria, including Coprococcus and Dorea (all P<0.001), and to Ruminococcus gnavus-like bacteria (P<0.05). In contrast, serological IgG responses against typical commensal, anaerobic and colonic microbial species were rather low, e.g. to the Lachnospiraceae members Roseburia and Blautia, to Faecalibacterium, as well as to Bacteroides. Patients with IBD showed more IgG-coating of Streptococcus, Lactobacillus, and Lactococcus bacteria compared to healthy controls (all P<0.05). No differences in IgG-coated bacterial fractions were observed between Crohn’s disease and ulcerative colitis, between active or non-active disease, nor between different disease locations. Conclusion The IgG immune response is specifically targeted at distinct intestinal bacterial genera that are typically associated with the small intestinal microbiota, whereas responses against more colonic-type commensals are lower, which was particularly the case for patients with IBD. These findings may be indicative of a strong immunological exposure to potentially pathogenic intestinal bacteria in concordance with relative immune tolerance against commensal bacteria.